PENGARUH QUENCHING SETELAH PENGELASAN TERHADAP KOROSI DI BAWAH INSULASI MEDIA AIR LAUT PADA BAJA A36 - Ridho, Arda Roshid (Journal of Renewable Engineering, 2024)
Corrosion in low-carbon steel is a significant issue in the industrial world, particularly in the oil, gas, refining, and chemical industries, as it leads to substantial financial losses. The total losses experienced by companies in Indonesia are estimated to reach 2-5% of the country's GDP. Corrosion arising from insulation damage, known as Corrosion Under Insulation (CUI), is challenging to detect but has a profound impact on industrial processes. Welding quality and corrosion resistance can be improved through post-weld heat treatment (PWHT). This research aims to investigate the influence of rapid cooling after welding low-carbon ASTM A36 steel on corrosion events under insulation using the "Water Immersion" method with seawater from the Muntok area, Bangka Belitung Islands Province, for 7 and 14 days. The welding process is performed using shielded metal arc welding (SMAW). Heat treatment is applied at 880°C for 60 minutes, as determined by the carbon equivalent calculation, followed by rapid cooling in seawater. Testing includes chemical composition analysis, non-destructive testing with dye penetrant on the welds, Brinell hardness testing, corrosion rate calculations, charpy impact testing, and metallography observations. The research results indicate that quenching enhances hardness and toughness while affecting the corrosion rate of the material after corrosion immersion, both with and without insulation. Material immersion exhibits a corrosion rate inhibition on the 14th day due to the formation of an oxide layer that hinders further degradation. Metallography observations reveal that after welding, phases formed include pearlite, acicular ferrite, and widmanstatten structures.